The Beauty of Birds : From "Birdscapes: Birds in Our Imagination and Experience." - Mynott, Jeremy (Princeton University Press, 2012)
Spring returns and with it the birds. But it also brings throngs of birders who emerge, binoculars in hand, to catch a glimpse of a rare or previously unseen species or to simply lay eyes on a particularly fine specimen of a familiar type. In a delightful meditation that unexpectedly ranges from the Volga Delta to Central Park and from Charles Dickens's Hard Times to a 1940s London burlesque show, Jeremy Mynott ponders what makes birds so beautiful and alluring to so many people. Princeton Shorts are brief selections taken from influential Princeton University Press books and produced.